CT scan examination on stroke patients - Arif Faisal Arif Faisal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
This study was conducted in patients with clinical stroke. The results showed that 61.3% patients had cerebral infarction, 33.0% hemorrhagic lesions and 5.7% was normal by CT scan examination. 12 of 29 hemorrhagic lesionswere associated with in [raven tri cular bleeding and these lesions have a poor prognosis.The cerebral infarctions were located mostly in capsula interna and nucleus le n tiforrnis, but the thalamus and capsula interna demonstrated as the main location for hemorrhagic lessons. The usefulness of CT scan in stroke lies especially in detecting the location, extension of lesion and in differentiating between ischemic and hemorrhagic lesions.Key Words: CT scan - in traventricular bleeding - hem iparesis - cerebral infarction - stroke